Analisis Cancel Culture di Era Digital Perspektif Etika Islam: Tinjauan Al-Qur’an dan Hadits - Zahratunnisa; Nasrulloh (Al-Kindi, 2026)
The dominance of cancel culture in digital spaces reflects a major shift in contemporary practices of moral correction while raising ethical concerns related to information reliability, justice, and the risk of digital harm. This study aims to reinterpret cancel culture through the ethical framework of amar makruf nahi mungkar to determine when it may operate as a legitimate and constructive form of resisting wrongdoing. Using a qualitative library-based approach, the research integrates thematic Qur’anic exegesis on hisbah, analysis of key hadith on moral responsibility, and multidisciplinary literature on digital behavior, mass psychology, and online public opinion. The findings indicate that cancel culture becomes ethically permissible when grounded in tabayyun, aligned with principles of justice, free from tajassus, and protective of human dignity against mob-driven excesses. The study further proposes a model of digital amar makruf nahi mungkar that emphasizes public education, data verification, restorative correction, and the prevention of informational harm. Its main contribution lies in connecting classical Islamic ethical principles with contemporary digital dynamics, producing a framework that guides ethical online engagement. The research concludes that cancel culture can serve as a legitimate mechanism of moral accountability when governed by maqāṣid al-sharī‘ah, while noting limitations concerning the absence of empirical data and the rapidly evolving digital landscape.